A rigid–flexible double-layer steric strategy promoting ethylene polymerization and copolymerization in alkane solvents. Issue 1 (15th November 2022) - Lu, Weiqing; Fan, Weigang; Dai, Shengyu
Abstract : A rigid–flexible double-layer steric strategy enables the practical application of late-transition metal ethylene (co)polymerization systems in industry. Abstract : In this study, a series of double-layered steric α-diimine nickel and palladium complexes containing bulky diarylmethyl moieties with remote 4-cycloalkyl and -phenyl substituents were designed and synthesized. The as-synthesized nickel complexes showed high activities ( ca. 10 6 g mol −1 h −1 ) and superior thermal stability, giving access to moderately branched polyethylenes with high molecular weights and narrow molecular weight distributions at high temperatures. With the rigid–flexible double-layered steric nickel catalysts, high temperature living polymerizations at 80 °C were achieved. The polyethylene materials yielded by these nickel catalysts at 80 °C exhibited outstanding tensile mechanical and elastic recovery properties (SR up to 86%). Correspondingly, the palladium complexes displayed moderate activities in ethylene polymerization, producing moderately branched polyethylenes with high molecular weights. The polyethylene materials yielded by palladium complexes at 60 °C exhibited good tensile mechanical properties and moderate elastic recovery values. In addition, these palladium complexes could also promote ethylene-polar monomer copolymerization, albeit with modest activity, yielding polar functionalized polyethylenes with moderate levels of branching densities, molecular weights, and incorporation ratios. Overall, the rigid–flexible double-layered steric nickel and palladium complexes with remote cyclohexyl substituents were found to have significantly higher activities than their rigid–rigid double-layered steric or monolayered dibenzhydryl counterparts in alkane solvents.